(untitled) (Journal of Nepalese Business Studies, 2020)
This study aims to explore the satisfaction and utilization of old age allowance among the Dalit Community in Pokhara, Nepal. For this purpose, Pokhara was purposively selected at first. Out of 553 Dalit respondents from randomly selected wards (13, 16, 26 and 29) of Pokhara Metropolitan City of Nepal who were getting old age allowance, information was collected purposively from 131 respondents using structured questionnaire through interview techniques. Hence, a multistage sampling technique was applied during the sample collection. Both descriptive as well as exploratory research design was used for the study. The majority of elderly Dalit are illiterate, unemployed and living jointly with their family. For most of the respondents, allowance is the major source of personal income. Most of them spend allowance for their own expenses. The majority of respondents are satisfied with the present allowance but still, there is the demand for increasing the allowances as it is so insufficient for their basic needs. On the basis of priority, most of the respondents spend their money on food for household consumption, health and medicines, transportation expenses, alms, clothes for self and tobacco, alcohol accordingly. Most of them have not faced difficulties in getting allowances. However, some of them have faced difficulties to travel to authorized office or bank to collect allowance due to their age, are not receiving allowance timely, late receiving allowance due to age error in documents, do not get paid the full amount and they feel a lot of administrative hassles. Hence the government should give attention to the problem faced by the respondents while receiving the old age allowance.